Identificación de peligros y evaluación de riesgos para la determinación de medidas de control en el Laboratorio de Ingeniería de Procesos Agroindustriales de la Facultad de Ciencias Agropecuarias, Universidad Nacional de Trujillo - González Rubio, Robert Henry (2015)
The Law N° 29783, on Safety and Health Occupational (OSH), according to its regulations, approved by Supreme Decree No. 005-2012-TR, says in his article 32, the employer must include the identification of hazards , risk assessment and control measures within its Management System for Safety and Health at Occupational (SGST). The aim of this study was to determine control measures, developing hazard identification and risk assessment based on Law N° 29783, Law on Safety and Health Occupational (OSH) for Process Engineering Laboratory Agroindustriales. The Occupational began with the revision of the current Standard RM No. 050- 2013 - TR, according to Law 29783, Law on Safety and Health at Occupational, which yielded the benchmark IPERC Matrix format containing the minimum information IPERC and mandatory registrations within the Management System for Safety and Health at Occupational (SGST). After the methodology used to obtain real information on existing conditions of Occupational in the laboratory of Process Engineering Agroindustrial. In this way it was possible to establish the necessary control measures to assessed risks, and improve levels of occupational safety and health of users.